Associations of health literacy, personality traits, and pro-individualism with the willingness to complete advance directives in Taiwan - Chen, Duan-Rung; Weng, Hui-Ching (BMC palliative care, 2023)
Studies indicated that patients with advance directives (ADs) have a generally better quality of life near death. Yet, the concept of ADs is relatively new in East Asian countries. This study examined the associations between health literacy, pro-individualism in end-of-life (EOL) decisions (i.e., EOL pro-individualism), and master-persistence personality traits with the willingness to complete ADs. The data is from a representative data of 1478 respondents from the 2022 Taiwan Social Change Survey. Generalized structural equation modeling (GSEM) was used to conduct path analysis. Nearly half of the respondents (48.7%) were willing to complete ADs. Health literacy has direct and indirect effects through EOL pro-individualism values on the willingness to complete ADs. Noncognitive factors such as mastery-persistence personality traits and EOL pro-individualism values enhanced the willingness to complete ADs. A personalized communication strategy, mindful of personality dimensions and cultural values, can address individual fears and concerns, promoting the benefits of advance care planning (ACP). These influences can provide a roadmap for healthcare providers to customize their approach to ACP discussions, improving patient engagement in AD completion.